Analyzing Stakeholder Roles and Collaboration in the Development of Village-Owned Enterprises in Indonesia - Cahyaningrum, Adhilia Mega; Gravitiani, Evi; Mulyanto, Mulyanto (Journal of Economics and Management Scienties, 2025)
The development of Village-Owned Enterprises (VoE) has emerged as a strategic instrument in Indonesia's rural transformation. However, its effectiveness and success remain uneven. This study employed a mixed-methods approach, incorporating stakeholder analysis using the MACTOR (Matrix of Alliances and Conflicts, Tactics, Objectives, and Recommendations) method. Primary data were collected through in-depth interviews with ten actors representing the pentahelix collaboration, comprising government, academics, business sector, community, and media representatives. The analysis showed that government actors served as the main drivers. Pioneering VoEs and their communities still rely on external support, while advanced VoEs were more independent and influential. The most supported key objectives among actors were the improvement of managerial skills and the dissemination of best practices in VoE management, while green business initiatives still received limited attention. These findings confirm that the success of VoE development depends on institutional capacity and effective collaboration among actors involved in achieving village economic independence. They also highlight the importance of strengthening stakeholder collaboration to accelerate rural development by aligning economic empowerment with social welfare and environmental responsibility.